Biodiversity and Health in the Face of Climate Change 2019
DOI: 10.1007/978-3-030-02318-8_20
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity and Health in the Face of Climate Change: Perspectives for Science, Policy and Practice

Abstract: Increases in non-communicable diseases, biodiversity loss and climate change are among the greatest global challenges society is facing today. At the same time, biodiverse natural environments can buffer the negative effects of climate change to society and support human health. Contributions in this volume demonstrate the growing interest in the impact of biodiversity on human health and wellbeing in the face of climate change. The chapters in this volume present and critically review the growing body of lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Consequently, a key research challenge is to investigate the causal pathways linking specific elements of biodiversity to human health [ 17 , 105 , 113 •] and test theoretical frameworks [ 18 ••, 116 •]. How exactly does biodiversity influence human physical, mental and social health?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, a key research challenge is to investigate the causal pathways linking specific elements of biodiversity to human health [ 17 , 105 , 113 •] and test theoretical frameworks [ 18 ••, 116 •]. How exactly does biodiversity influence human physical, mental and social health?…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the extensive research on ecosystem service benefits to human health and well-being often lacks specifics on the biodiversity involved [ 1 , 16 ]. Accordingly, we see a need to further develop knowledge of the ways in which specific elements of biodiversity itself matters for human health [ 17 , 18 ••]. A first, simplistic approach to measuring nature, for example as the amount of greenspace, has enabled a surge of new research and can serve as an important indicator for urban health planning goals [ 15 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this talk, the presenter identified the inequalities between different socio-economic groups in view of urban green infrastructures. The benefits of green spaces to human health outweighed the disadvantages and this was supported by Kabisch in chapter 5 of Marselle et al [20] which revealed the health effects of green space as an adaptation to different socio-economic and socio-demographic population groups. The presentation also showed that vulnerable groups of people, including the aged who live in less green areas with lower numbers of trees, are mostly impacted by the reduced quality of life.…”
Section: Gender Equality and Urban Green Infrastructuresmentioning
confidence: 91%
“…physical activity) and human health (Step 4). Most importantly, data-driven experimental research approaches employing longitudinal, intervention and randomized controlled trial experimental studies in the field and the lab are needed to test these conceptual pathways and their synergistic interaction to understand biodiversity-health linkages (Aerts, Honnay and Nieuwenhuyse, 2018;Marselle, Stadler, et al, 2019a;Müller et al, 2019).…”
Section: Recommendations For Future Researchmentioning
confidence: 99%